Ultrafast synthesis of fluorine-18 doped bismuth based upconversion nanophosphors for tri-modal CT/PET/UCL imaging in vivo. Issue 50 (6th June 2019) - Li, Yuhao; Liu, Jie; Qin, Xiaojia; Deng, Yong; Zhang, Jianping; Sun, Yun
Abstract : A fluorine-18 doped bismuth upconversion luminescence (UCL) nanoprobe ( 18 F-UNBOF) was quickly synthesized within 1 min at room temperature, and it could be utilized for computed tomography (CT), positron emission tomography (PET) and UCL imaging in vivo . Abstract : A fluorine-18 doped bismuth upconversion luminescence (UCL) nanoprobe ( 18 F-UNBOF) was quickly synthesized within 1 min at room temperature. 18 F-UNBOF showed strong X-ray attenuation characteristics, stable radioactive 18 F-labeling abilities and UCL properties. 18 F-UNBOF nanoparticles could be utilized for tri-modal CT/PET/UCL imaging in vivo .